(untitled) (Bangladesh Journal of Botany, 2020)
The petroleum ether, chloroform and ethyl acetate soluble fractions of methanolic extract of Litsea lancifolia Roxb. leaves were subjected to different pharmacological screenings to explore its potential as anti-oxidant, antimicrobial, peripheral analgesic, hypoglycemic and CNS depressing agent. The ethyl acetate soluble fraction showed highest total phenolic content and free radical scavenging activity compared to the standard, acetyl salicylic acid. Potential antimicrobial activity was shown against P. aeruginosa (23.50 mm), E. coli (22.33 mm), B. cereus (18 mm) and S. paratyphi (18 mm). The crude extract demonstrated significant peripheral analgesic (p < 0.01) activity with 69.45 and 77.96% inhibition of acetic acid-induced writhing at 100 and 200 mg/kg b.w., respectively. The crude methanolic extract also showed significant hypoglycemic activity (p < 0.01) at a dose of 500 mg/kg/day on the 7th day of treatment. All the organic soluble fractions exhibited noteworthy (p < 0.001) CNS depressant activity. Taken together, the plant can be considered as a good material for further chemical investigation to isolate the bioactive constituents.